Serologic testing for symptomatic coccidioidomycosis in immunocompetent and immunosuppressed hosts - Blair, Janis E. (Springer Netherlands, 2006)
Serologic studies are an important diagnostic tool in the clinical evaluation and follow-up of persons with coccidioidomycosis. Numerous types of serologic tests are available, including immunodiffusion, enzyme immunoassay, and complement fixation. We conducted a retrospective review of the results of 1,797 serologic tests spanning 12 months from the onset of coccidioidomycosis in 298 immunocompetent and 62 immunosuppressed persons with symptomatic infection. Using the onset of symptoms as a reference point, we plotted the positive or negative serologic results over time for both groups. Compared with the immunocompetent group, immunosuppressed persons had lower rates of seropositivity for every type of test during the first year after onset of symptoms for coccidioidomycosis, although many results did not achieve statistical significance. Combining the results of these tests increased the sensitivity of the serologic evaluation in immunocompromised patients. Immunosuppressed persons have the ability to mount a serologic response to coccidioidomycosis, but in some circumstances, multiple methods may be required to improve detection.